Situational crime analysis of poaching within Territorial Use Rights Fisheries (TURFs) - Vallejos, Tomás; Nahuelhual, Laura; Gelcich, Stefan; Oyanedel, Rodrigo (Frontiers in Marine Science, 2024)
Introduction Illegal, unreported, and unregulated (IUU) fishing poses a significant threat to marine resource management globally. Environmental criminology plays a vital role in understanding and mitigating IUU activities by focusing on the contextual elements surrounding these crimes. This study examines the dynamics of poaching within areas managed through Territorial User Rights for Fisheries (TURFs), with a specific emphasis on the loco (Concholepas concholepas) fishery in Chile. Methods Employing Crime Script Analysis (CSA) as the primary methodological lens, this research meticulously deconstructs the criminal process involved in TURFs poaching operations. CSA is used to identify key elements, providing a comprehensive understanding of poachers modus operandi. Additionally, by integrating CSA with Situational Precipitators of Crime (SPC), the study identifies critical factors such as environmental conditions, socio-economic disparities, and enforcement weaknesses that shape poaching opportunities within TURFs. Results The analysis reveals a complex interplay between SPC factors, underscoring their role in shaping poaching dynamics. Key findings highlight the importance of specific environmental conditions, socio-economic disparities, and enforcement weaknesses in facilitating poaching activities. The study identifies various tactics and strategies employed by poachers and the roles of different actors involved in the poaching process. Discussion Building upon these findings, the study proposes a comprehensive Situational Crime Prevention (SCP) framework aimed at effectively combating TURFs poaching. The framework emphasizes the importance of striking a careful balance between restrictive and inclusive measures to mitigate potential negative consequences. The study contributes valuable insights into understanding and addressing IUU fishing, particularly within TURFs in Chile.